Double Jeopardy? Disproportionality in First Juvenile Court Involvement by Disability Status. (July 2019) - Kincaid, Aleksis P.; Sullivan, Amanda L.
The overrepresentation of youth with disabilities in the juvenile justice system is a persistent concern, but estimates of their involvement vary dramatically due to differences in how disability is conceptualized and when involvement in juvenile justice is measured. This study linked juvenile court and educational records for 230, 760 students in one state to describe the involvement of students with and without disabilities in juvenile court. Overrepresentation of students with disabilities was not robust to sociodemographic controls (relative risk ratio [RR] = 1.07) but varied by disability category such that students with emotional or behavioral disorders (RR = 1.98) and other health impairments (RR = 1.12) remained overrepresented. Students with disabilities were charged with more severe offenses than their peers without disabilities and were more likely to be petitioned to court with a higher degree of offense even after controlling for the type of offense. Implications for policy, practice, and research are discussed.